PECULIARITIES OF TECHNICAL DRAWING PERFORMANCE METHODS OF DRAWING - Mastipanova, A.V. (Pedagogy of Higher and Secondary Education, 2007)
Similarity and difference o f artistic and technical designs and also some particularities of fulfilling technical design in the drawing studies for the purpose of improvement o f perception of technical design characteristic features by the students of artistic orientation were considered in the article.